Frequency and genotypes of Chlamydia trachomatis in patients attending the obstetrics and gynecology clinics in Jalisco, Mexico and correlation with sociodemographic, behavioral, and biological factors - Néstor Casillas-Vega; Rayo Morfín-Otero; Santos García; Jorge Llaca-Díaz; Eduardo Rodríguez-Noriega; Adrián Camacho-Ortiz; Ma de la Merced Ayala-Castellanos; Héctor J. Maldonado-Garza; Jesús Ancer-Rodríguez; Guadalupe Gallegos-Ávila; Alberto Niderhauser-García; Elvira Garza-González (BMC, 2017)
Abstract Background Chlamydia trachomatis is the causative agent of the most common bacterial sexually transmitted infection worldwide. The aim of this study was to investigate the frequency and genotypes of C. trachomatis in patients attending an obstetrics and gynecology clinic in Jalisco, Mexico and correlates them with sociodemographic, behavioral, and biological factors. Methods C. trachomatis detection was performed in endocervical samples from 662 patients by direct fluorescence assay (DFA) and two PCR assays that amplified the phospholipase D endonuclease superfamily protein (PLDESP) and OmpA genes. Positive samples were genotyped using PCR-restriction fragment length polymorphism assays. Sociodemographic, behavioral, and biological data were collected. Results The mean age of the study population was 31 (range, 14-78) years. C. trachomatis positivity was detected by DFA in 16.7% (n = 111), PLDESP gene amplification in 14.2% (n = 94), and OmpA gene amplification in 14.5% (n = 96) of the population. Eight C. trachomatis genotypes were detected: E (39.6%), F (29.2%), D (15.6%), K (6.3%), L2 (3.1%), G, J, and I (2.1% each). C. trachomatis infection was associated with age, marital status, pregnancy, and hormonal contraceptive use (all p = 0.01); intrauterine device use and previous premature birth (both p = 0.03); and infection during pregnancy, previous ectopic pregnancy, pelvic inflammatory disease (PID), and green vaginal discharge (all p = 0.04). C. trachomatis genotype K was more likely to be detected in women histories of ≥2 sexual partners, genotype F was more likely in pregnant women, genotype L2 was more likely in women with PID, genotype D was more likely in women who had had infection during previous pregnancies, and genotype E was more likely in those with previous ectopic pregnancies and green vaginal discharge (all p = 0.01). Conclusions The frequency of C. trachomatis in our population was higher than previously reported worldwide, but within the range reported for Mexico. Genotype E was detected most frequently in the study population. Infection by C. trachomatis and C. trachomatis genotypes K, F, D, and E was strongly associated with multiple sociodemographic, behavioral, and biological factors. C. trachomatis genotype L2 was detected in women with PID.